Mitogen-Activated Protein Kinase Kinase 4 Gene Polymorphism and Cancer Risk. Issue 44 (November 2015) - Geng, Peiliang; Ou, Juanjuan; Xie, Ganfeng; Li, Jianjun; Zhao, Xiaoxin; Xiang, Lisha; Liao, Yunmei; Wang, Ning; Liang, Houjie
Abstract : Abstract: A number of epidemiological studies have assessed the association of −1304T > G polymorphism in the MKK4 gene and risk of cancer, but the results lack of statistical power due to the limited subjects used in these studies. This study was devised to identify the genetic effects of the −1304T > G polymorphism on cancer risk in a large meta-analysis. Eligible studies were identified by searching both Chinese and English databases. General as well as subgroup analyses were performed for 8 independent case–control publications with a total of 4623 cases and 5256 cancer-free controls. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to estimate the association. Overall, this meta-analysis showed that the association between the −1304T > G polymorphism and cancer risk was statistically significant (GG vs TT: OR = 0.63, 95% CI, 0.52–0.75; GG + TG vs TT: OR = 0.85, 95% CI, 0.79–0.91; GG vs TG + TT: OR = 0.67, 95% CI, 0.56–0.80; G vs T: OR = 0.82, 95% CI, 0.77–0.88; TG vs TT: OR = 0.86, 95% CI, 0.79–0.93). Our meta-analysis reveals that the presence of the −1304T > G polymorphism is likely to decrease risk of cancer. Future larger studies are necessary to validate the current finding.